Penerapan Model Pembelajaran Koopratif Tipe NHT (Numbered Head Together) terhadap Hasil Belajar Chest Pass dan Bounce Pass Permainan Bola Basket pada Siswa Kelas XI IPA 1 dan IPA 2 SMA Negeri 1 Mendoyo - Kristiawan, I Putu Febrian Candra; Indrawan, I Ketut Addy Putra; Repiyasa, I Wayan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the application and effectiveness of the Numbered Heads Together (NHT) learning model in improving learning outcomes of the chest pass and bounce pass techniques in basketball among students of XI IPA 1 and XI IPA 2 at SMA Negeri 1 Mendoyo. The research design used a Matching Pretest-Posttest Control Group Design. Data collection procedures were carried out by administering a pretest before the treatment and a posttest after the treatment. Data analysis was performed using a paired sample t-test, followed by an independent sample t-test. The results of the study indicate that the implementation of the NHT model can create a more interactive and collaborative learning environment, making students more active in the learning process, exchanging information, and understanding the material better. Statistical tests (paired sample t-test and independent sample t-test) proved that there is a significant improvement in learning outcomes in the experimental group compared to the control group, both in chest pass and bounce pass skills